Impact of technological advancements on environmental degradation: evidence from ASEAN - Othman, Norashida; Hewage, Rishan Sampath; Pyeman, Jaafar; Murdipi, Rafiqa (e-International Publishing House, Ltd., 2022)
This research investigates the long-run and short-run effects of technological advancements on environmental degradation in ASEAN countries. The research was conducted using Pooled Mean Group (PMG) panel data estimation methodologies, and the data set used in this study includes annual data from 2000 to 2019. Results revealed that the development of technology reduces the environmental degradation of ASEAN countries. Improvements in technology and more money for research and development through domestic savings lead to increased environmental quality in the long run. Therefore, this study concludes that policymakers should increase the investment in technological innovations to reduce environmental degradation.